Retrospective study of the healing processes of endodontically treated teeth characterized by osteolytic defects of the periapical area: four-year follow-up. Issue 1 (2nd January 2017) - Gusiyska, Angela; Gateva, Natalia; Kabaktchieva, Rossitza; Stanimirov, Pavel; Raychev, Ivan
ABSTRACT: One of the main objectives of primary endodontic treatment is the prevention of periapical tissue changes which, in the majority of clinical cases in general practice, does not take place because of the availability of a wide range of precise endodontic instruments. The healing process of the periapical area in teeth with inflammatory bone destruction is still a challenge in contemporary endodontic practice. The aim of this retrospective study was to assess the postoperative healing process of teeth with osteolytic defects in the periapical area. Eighty-nine endodontically treated teeth ( n = 89) were included in the study. The teeth with necrotic pulp and without detectable periapical lesions were successfully treated in 92.9% of the cases. All of the incisors, canines and premolars showed significantly higher probabilities of success (97.8%) than molars (90.9%; P = 0.036). In all monitored teeth, the maxillary first molars with periapical index (PAI) 1 (80.2%), mandibular premolars with PAI3 (75%) and mandibular molars with PAI5 (75%) had the lowest rates of treatment success. In this study, the success rate of teeth with pulp necrosis complicated with a periapical lesion was 89.75% ( P > 0.05). The analysis of the results from this study confirmed that the exact orthograde retreatment of the cases with osteolytic defects of the periapical area led to satisfactory healing and regeneration in the periapical area.